Identification of he-ne laser based mutation induced bacteria against grape disease (Bangladesh Journal of Botany, 2024)
In the present study six bacterial strains from the soil of grape orchard were isolated and identified. Their antagonistic ability against Uncinula necator and Plasmopara viticola which cause downy mildew and powdery mildew of grapes, respectively were studied. Through phenotypic, physiological and biochemical studies, SF6 strain was identified as Bacillus subtilis which can effectively inhibit the growth of Uncinula necator and Plasmopara viticola of grapes. In order to enhance the antagonistic ability of the SF6 strain, mutation was induced by He-Ne laser radiation and, six mutant strains were obtained. Among the six mutant strains, SF66 showed the strongest antagonistic activity to Uncinula necator and Plasmopara viticola of grapes with its genetic stability. The finding of this research provides important impetus for the development of beneficial antagonistic microorganisms through He-Ne laser radiation breeding.Bangladesh J. Bot. 53(1): 33-40, 2024 (March)